Association between transabdominal uterine artery Doppler and small-for-gestational-age: a systematic review and meta-analysis - Ruijuan Zhi; Xiangping Tao; Qingtao Li; Ming Yu; Honge Li (BMC, 2023)
Abstract Background The association between uterine artery Doppler (UtA) measurements and small for gestational age (SGA) has not been quantitatively analyzed throughout the whole pregnancy. This systematic review and meta-analysis aims to comprehensively explore the association between UtA measurements and SGA in the first, second, and third trimesters. Methods Studies were searched from Pubmed, Embase, Cochrane Library, and Web of Science. Weighted mean difference (WMD), odds ratio (OR), and relative risk (RR) with 95% confidence interval (CI) were used as the effect size. Heterogeneity of all effect sizes was tested and quantified using I2 statistics. Sensitivity analysis was conducted for all outcomes, and publication bias was evaluated using Begg's test. Results A total of 41 studies were finally included in our meta-analysis. In the first trimester, mean PI was significantly higher in the SGA group than the non-SGA group (WMD: 0.31, 95%CI: 0.19-0.44). In the second trimester, odds of notch presence (OR: 2.54, 95%CI: 2.10-3.08), mean PI (WMD: 0.21, 95%CI: 0.12-0.30), and mean RI (WMD: 0.05, 95%CI: 0.05-0.06) were higher in the SGA group. Also, abnormal UtA measurements were associated with the increased odds of SGA (all P < 0.05). In the third trimester, PI z-score (WMD: 0.62, 95%CI: 0.33-0.91) and PI MoM (WMD: 0.08, 95%CI: 0.06-0.09) showed a significant increase in the SGA group. The odds of SGA were higher in the women with mean PI > 95% (OR: 6.03, 95%CI: 3.24-11.24). Conclusions Abnormal UtA measurements were associated with high odds of SGA, suggesting that UtA might be an adjunctive screening method for SGA in the whole pregnancy.